First record of fall armyworm (Spodoptera frugiperda) in Indonesia and its occurence in three provinces. Issue 1 (March 2020) - Sartiami, D; Dadang,; Harahap, IS; Kusumah, YM; Anwar, R
Abstract: The occurrence of a new invasive pest species of corn, the fall armyworms Spodoptera frugiperda (Lepidoptera: Noctuidae) in Indonesia is reported. Survey in 3 provinces in Indonesia: West Sumatera, Banten and West Java were conducted from March to June 2019. The first record of this pest was in 26 March 2019 in West Sumatera. Larvae were collected from each of those locations and field symptoms of damage on corn in the field were observed. Larvae were brought to and reared individually in Insect Biosystematics Laboratory of Plant Protection Department, Faculty of Agriculture, IPB University. Identification of fall armyworm employed morphological and molecular analysis. Identification of the larva based on morphological characters of larvae from 3 provinces confirmed the identity of the pest. The pest as fall armyworms, while the molecular analysis indicated that Banten samples belonged to the 'rice strain'. Collected larvae from Banten were infected by Metarhizium rileyi . The infested plants in the field showed the typical damage symptoms caused by the fall armyworm.